UPAYA PENCEGAHAN STROKE PADA PENDERITA HIPERTENSI DENGAN MODEL TERAPI KELOMPOK (INTENSIVE PROBLEM SOLVING GROUP) DI WILAYAH PUSKESMAS KREMBANGAN SELATAN - Asnani .; Loetfia Dwi Rahariyani; Hilmi Yumni (JURNAL PENELITIAN KESEHATAN, 2015)
Stroke / evA are the symptoms of nervous system function deficits caused by cerebrovascular disease.One of the causes of stroke are hypertension. That people with hypertension do not have a stroke it isnecessary to make effective prevention group therapy model in the community at risk. The purpose ofresearch is to identify the prevention of stroke in hypertensive patients with group therapy models(Intensive Problem Solving Group). This research design "Pretest-Posttest Design". T!1e population of allpatients with hypertension who checked himself in PHCKrembangan Surabaya, the number of samples10-15 men / women and purposive sampling technique sampling, group therapy dependent variable,independent variable levels of knowledge about hypertension and stroke prevention, mode of datacollection by using questionnaires open, closed and discussiongroups. Researchdata shows an increase inthe level of knowledge of hypertensive patients after group therapy, efforts are being made to preventstroke include Diit food (65%), regular exercise (54%), check regularly (77%), consumption of drugs on aregular basis (92%) Management of conflict / stress (59%), Maintaining healthy behavior (61%), balanceof activity and rest (56%), and the results of the analysis of the level of knowledge of hypertensivepatients before and after treatment groups using a statistical test PairedT test obtained P values: 0,000,where H1 is accepted, meaning that there is a difference between the level of knowledge abouthypertension before and after group therapy.Keywords: Hypertension, level of knowledge, prevention of stroke.